(untitled) - Parekh, L. R. (Darya Ganj, New Delhi, 2000)
Contents of material: Indexing and abstracting. Automatic indexing and automatic abstracting. Principles of indexing. Periodicals listing and accessioning. Online computer service. Dialog, searching and bibliographic display. Books. Bibliographic control. Abstracting functions. Acquisition system. Future of indexing and abstracting service.
Keywords: Abstracting,Indexing